Tanshinlactone triggers methuosis in breast cancer cells via NRF2 activation - Lin, Wanjun; Huang, Zifeng; Zhang, Xuening; Zheng, Dayuan; Yang, Yanchao; Shi, Meina; Yang, Dongfang; Chu, Tong; Ma, Wenzhe (Frontiers in Pharmacology, 2025)
BackgroundTanshinlactone is a compound derived from the herb Salvia miltiorrhiza. Breast cancer is the most prevalent malignancy among women globally. While significant strides have been made in breast cancer management, these interventions are often impeded by substantial adverse effects that undermine patients’ quality of life and confront limitations due to the eventual development of multi-drug resistance. Catastrophic macropinocytosis, also called methuosis, as a nonapoptotic cell death associated with cytoplasmic vacuolization, has gained increasing attention, largely because of its potential importance in cancer therapy.MethodsThe effect of tanshinlactone on the growth of human cancer cells was evaluated using sulforhodamine B and colony formation assay. Fluorescent dyes are used to label macropinosomes and lysosomes. Phase contrast, confocal and transmission electron microscopy were employed to observe cell morphological changes. RT-PCR, western blot, lentiviral-mediated gene overexpression, and pharmacological inhibitor assays were comprehensively designed to regulate the identified signaling pathways and confirm the mechanism of tanshinlactone. Human breast cancer cell lines-derived xenograft tumor explants assay was used to evaluate the compound’s efficacy and to assess the induction of methuosis via NRF2 activation by tanshinlactone.ResultsTanshinlactone selectively inhibits the growth of ER+ and HER2+/EGFR + breast cancer cells while showing limited cytotoxicity against other cancer types and normal cells. The selective anti-breast cancer activity is associated with the induction of methuosis, characterized by cytoplasmic vacuolization due to dysfunctional macropinocytosis. This process is mediated by the activation of the transcription factor NRF2, leading to the formation of macropinosomes that fail to fuse with lysosomes or recycle to the plasma membrane, resulting in cell death. The in vitro induction of methuosis via NRF2 activation was replicated in a murine xenograft explants model. Additionally, tanshinlactone demonstrated effectiveness against lapatinib-resistant breast cancer cells, suggesting its potential as a therapeutic agent for overcoming drug resistance in cancer treatment.ConclusionTanshinlactone as a novel therapeutic agent, is capable of selectively inhibiting ER+ and HER2+/EGFR + breast tumors through a unique mechanism of inducing catastrophic macropinocytosis. This regimen holds promise for targeted therapy with minimized side effects and offers a new therapeutic avenue for breast patients with drug-resistant diseases.